Early Childhood Character Building through Roadshow Islamic Telling Stories - Rahmawati, Lilis; Fuad, Nurul (EDUCATIO : Journal of Education, 2023)
The escalating decline in moral values represents a significant challenge confronting society, particularly in the context of educating children. Therefore, instilling character in children from an early age is of paramount importance, and one effective method to achieve this is through the use of books containing relevant stories within the framework of Islamic telling roadshows. The aim of this research is to design and test a book containing 10 stories of the companions of the Prophet, guaranteed to enter paradise, as an effective tool for character education in children. The study adopts the Research and Development (RnD) methodology, encompassing various stages, commencing with the identification of potential and issues. Throughout the research, pertinent data is collected, and the book's design is validated by subject matter experts (93%) and media experts (96%). Following revisions based on expert input, the book is tested by educators as users, resulting in a 100% approval rating. The evaluation outcomes reveal that the book makes a positive contribution to character development in children, with an 88% success rate. The research findings underscore the book's effectiveness in enhancing children's moral and character development, providing a positive contribution to educating children with strong morals and good character.